Uporabnost in učinkovitost malih prirejenih iger v nogometu - Ferk, Janez (Šport (Ljubljana), 2019)
Small-sided games in football (known as "game forms") have become a popular training method. The fact that this training method resembles a football match is attractive for players and coaches alike. The latter often search for the shortest path to high performance in the game, and small-sided games enable them to achieve this during the preparation period, when the desired intensity can be achieved through play, or during the competitive season when the intention is to restore physical fitness and determine tactical principles in the game. In small-sided games the space is limited and the number of players lower, along with other limitations and rules. The most important task of the coach is to come closer to the set objectives as much as possible with proper game organisation. They must also recognise when this type of training is not suitable. The contribution presents the influences on the conditioning, technical and tactical preparations of football players. Moreover, it identifies the effects of individual limitations and the advantages of small-sided games compared to matches or other training methods.
Keywords: conditioning; football; game forms; igralne oblike; kondicijska priprava; male prirejene igre; nogomet; small-sided games; sport; šport; tactical preparations; taktična priprava; technical preparations; tehnična priprava